THE ANALYSIS OF COLLOCATION IN DISCUSSION PAPERS AT AL MARKAZ FOR KHUDI ENLIGHTENING STUDIES (MAKES) IN MAKASSAR - Akbar, Taufik; Rampeng (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2021)
The research aimed is to know lexical collocation in writing production committed by MAKES Member at al Markaz for Khudi Enlightening Studies (MAKES) Makassar. The result of this research is expected to give benefits for the EFL/ESL learner especially in using English collocation in all English skills. This research used descriptive qualitative method. The populaton of this research is about 30 respondents and sampling 15, period of 2015-2016. In this research the writer took only 4 selected writing productions to be analyzed. The analysis data indicated that there were lexical collocations in each informant’s writings. Although, there were a tendency of difficulty of informants to use lexical collocation type L3. These showed by the higher number of errors occurrence in this type. Moreover, the errors occurrence, in fact, mostly, affected by the lack of understanding of the using collocation, negative transfer from their native language and the improper way in assembling the two-words. It was stated that the MAKES members need to improve their English comprehensively, particularly the awareness of using the correct and effective lexical collocation in their writing production.